Quantitative Differential Thermal Analysis; An Experimental Assessment - Vaidya, Viwek. V. (My University, 2016)
The principle of quantitative differential thermal analysis is based on the fundamental principles of calorimetry. These principles cannot be rigorously applied while performing differential thermal analysis due to the complexities in the design, which leads to erroneous results.
A modified DTA apparatus was built to take into account some of the errors neglected in the present day apparatii. The heat transfer characteristics of the apparatus were found to limit in situ measurements of power thermal conductivity. It was also demonstrated that the negligence of heat lost to the DTA block from the sample cell during an exothermic reaction and heat gained from the DTA block by the sample cell during endothermic reactions lead to large errors in quantitative estimations.
A modified apparatus was designed to take the aforementioned heat losses into account. The apparatus was calibrated with CaCO3 endotherm and kaolinite exotherm and tested on the SrCO3 rhombic ↔ trigonal inversion endotherm. The result was found to be in good agreement with accepted literature values.
Title: Quantitative Differential Thermal Analysis; An Experimental Assessment, Author: Viwek V. Viadya, Location: Thode